Impact of carbon concentration on optical and zeta potential properties of carbon quantum dots - Zaini, Muhammad Safwan; Jian, Low Yiin; Liew, Josephine Ying Chyi; Ahmad Kamarudin, Mazliana (Taylor and Francis, 2024)
Carbon quantum dots (CQDs) are fluorescent nanoparticles with diverse applications in multiple fields. The optical and physical properties of CQDs are influenced by several factors, such as the synthesis method, surface passivation and particle size. This study explores how carbon concentration affects the properties of CQDs. The CQDs were synthesized through a carbonization process with carbon concentrations varying from 0.03 to 0.15 g/ml. The samples of CQDs were characterized by using high resolution transmission electron microscopy (HRTEM), photoluminescence (PL) spectroscopy, zeta potential, dynamic light scattering (DLS) and Fourier transform infrared spectroscopy (FTIR). The results indicate that carbon concentration significantly impacts the optical properties and zeta potential of CQDs. Specifically, higher carbon concentrations result in increased fluorescence intensity and larger particle size. HRTEM images reveal that the average size of the CQDs is below 10 nm, consistent with DLS measurements. These findings suggest that carbon concentration can serve as a straightforward and effective parameter for tuning CQDs properties, with potential applications in bioimaging, sensing and optoelectronics.